Controlled Release Matrix Drug Delivery System – a Review - A.Madhusudhan Reddy (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Oral controlled release drug delivery system becomes a very promising approach for those drugs that are given orally but having the high dosing frequency and shorter half life. Matrix tablets serves as an important tool for oral controlled release dosage forms. Problems like patient compliance drug targeting, local side effects, frequent administration and fluctuations in blood concentration levels, associated with their counter parts, the conventional dosage forms were rectified. Tablets offer the lowest cost approach to controlled and sustained release dosage forms. Matrix tablets controlled release has given a new breakthrough for novel drug delivery system in the field of pharmaceutical technology. This review focus on the various types of matrix system based on polymer used and porosity of matrix system i.e hydrophilic, hydrophobic, fat wax, porous, nonporous, pH sensitive. An effort has been made to consolidate different types of patents granted across the globe for last thirty years in the field of matrix system viz. tablets, pellets etc